(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
The aesthetic reflection in the eighteenth century is deeply traversed by an experience perceived as capable of disrupting the disciplinary and cognitive system of early modernity: To feel the “own body,” that is, to feel its state of well-being or discomfort means to somehow modify from the inside the anthropological project of the Century of Enlightenment and to create the space and the lexicon of a modality of relationship (play, aesthetic illusion) that redefines the relationship with oneself and the context of construction of a future community. Whereas “Knowledge” and “Will” articulate the same strategy based on the relationship between the spiritual activity of a subject and the semiotic properties of an object, the orientation towards the condition of one’s own body defines in the play and in the aesthetic illusion the space of an imaginative reserve which is above all a reserve of time and mode of construction for a future sharing. Moses Mendelssohn’s thought constitutes the exemplary arrival point of an era of theoretical research that we are interested in investigating not only in terms of the solutions it has found for his time, but also in relation to the open problems, which continue to question our time.